Designing a Marketing Strategy for Xiaomi Mobile Phones Based on Market Share Analysis Using Markov Chain in Indonesia: Perancangan Strategi Pemasaran Handphone Xiaomi Berdasarkan Analisis Pangsa Pasar Menggunakan Markov Chain di Indonesia - Herowati, Evy; Wahyudi, Rahman Dwi; Akbar, Muhammad Syahrul (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2025)
In this study, a marketing strategy for Xiaomi mobile phones in Indonesia was designed based on market share analysis using the Markov Chain method and SWOT analysis. The mobile phone market is very competitive, so to maintain and increase market share, it is necessary to understand the dynamics of consumer movement between brands. The Markov Chain method is used to model the possibility of customer movement from one brand to another based on historical market share data of several major brands, including Xiaomi, iPhone, Samsung, Oppo, Asus, and Vivo. After the Markov Chain, it is continued with SWOT Analysis and Marketing Strategy Design. Some strategies that Xiaomi can use include creating a user-friendly Xiaomi image, actively advertising and promoting both electronic and non-electronic media, using public figures as brand ambassadors, creating recycling movements, and creating a campaign. This strategy successfully increased consumers' probability of choosing Xiaomi as their main choice.